From containers to content to context: The changing role of libraries in eScience and eScholarship. Issue 2 (2014) - ,
Abstract : Purpose – The aim of this paper is to reposition the research library in the context of the changing information and knowledge architecture at the end of the "Gutenberg Parenthesis" and as part of the rapidly emerging "semantic" environment of the Linked Open Data paradigm. Understanding this process requires a good understanding of the evolution of the "document" notion in the passage from print based culture to the distributed hypertextual and RDF based information architecture of the WWW.Design/methodology/approach – These objectives are reached using literature study and a descriptive historical approach as well as text mining techniques using Google nGrams as a data source.Findings – The paper presents a proposal for effectively repositioning research libraries in the context of eScience and eScholarship as well as clear indications of the proposed repositioning already taking place. Furthermore, a new perspective of the "document" notion is provided.Practical implications – The evolution described in the contribution creates opportunities for libraries to reposition themselves as aggregators and selectors of content and as contextualising agents as part of future Linked Data based scholarly research environments provided they are able and ready to operate the related cultural changes.Originality/value – The paper will be useful for practitioners in search of strategic guidance for repositioning their librarian institutions in a context of ever increasing competition for scarce funding resources. Acknowledgements : This paper is in large parts based on the author's keynote at the 10th International Bielefeld Conference delivered on April 24, 2012.